2011
DOI: 10.1007/s12520-011-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the pigments in a Ptolemaic Egyptian Book of the Dead papyrus

Abstract: A relevant subject of study in the sphere of ancient Egyptian painting technology is given by the evolution of the palette across New Kingdom, Ptolemaic and Roman periods. Functionally to secondary factors such as geographic occurrence of minerals and type of associated surface, the employment of certain painting materials provides relevant insights into particular issues such as relative dating of the object and social rank of the owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…On the basis of the presented data, we propose that orpiment was originally mixed with realgar to create the orange pigment. It is theoretically and experimentally well established that realgar transforms, via the intermediate byproduct χ‐As 4 S 5 , to pararealgar under the influence of light 44,45 . It is noteworthy to mention that the other byproduct reported during this phase transition is arsenolite (As 2 O 3 ), 46 which has not been detected in the current study.…”
Section: Resultsmentioning
confidence: 43%
“…On the basis of the presented data, we propose that orpiment was originally mixed with realgar to create the orange pigment. It is theoretically and experimentally well established that realgar transforms, via the intermediate byproduct χ‐As 4 S 5 , to pararealgar under the influence of light 44,45 . It is noteworthy to mention that the other byproduct reported during this phase transition is arsenolite (As 2 O 3 ), 46 which has not been detected in the current study.…”
Section: Resultsmentioning
confidence: 43%
“…Blue pigment: a-b) light blue pigment layer with coarse morphology, different chromatic degrees ranging from blue to pale green crystals and glaze matrix between the blue crystals; c-d) dark blue pigment layer with coarse morphology, different crystal blue color, white and transparent yellow. a c b d 800-850 °C a dark blue pigment layer with coarse surface morphology appears with different crystal colors composed of blue, white and transparent yellow [26][27][28][29].…”
Section: Ground Layersmentioning
confidence: 99%
“…In the 1970s it was shown that both structures were in fact built from the same structural units, but upon different principles 3 . Thereupon, realgar was thought to light-degrade to orpiment and arsenic oxide (As 2 O 3 , arsenolite), which is consistent with the color change from red/orange to orange/yellow, however this is not the case [12][13][14][15] .…”
Section: Preliminary Considerationsmentioning
confidence: 99%
“…It is a useful tool to identify and characterize pigments, elemental chemical composition, toxicity, usage, etc. Microsampling and non-destructive techniques are also important variables to consider when dealing with cultural patrimony and unique objects while pursuing chemical characterization and analyses of ancient samples [1][2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%